2007
DOI: 10.1111/j.1600-0668.2006.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoor organophosphate and polybrominated flame retardants in Tokyo

Abstract: Polybrominated biphenyls (PBB) and polybrominated diphenyl ethers (PBDE) are commonly used as flame retardants in plastics. The use of these two compounds in electric appliances will be banned in 2007 by the EU Directives on waste electrical and electronic equipment (WEEE) and on the restriction of the use of certain hazardous substances (RoHS) in electrical and electronic equipment. In Japan, the use of PBB was banned and that of PBDE diminished in the early 1990s by the self-imposed controls of the Japanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 20 publications
7
102
1
Order By: Relevance
“…13674-84-5). These compounds are present in the formulation of flame retardants, can be emitted from indoor furnishings and electrical equipment, and have 18 been reported in indoor air and dust (Staaf and Ostman 2005;Saito et al 2007). …”
Section: Reactions On Chamber Wallsmentioning
confidence: 99%
“…13674-84-5). These compounds are present in the formulation of flame retardants, can be emitted from indoor furnishings and electrical equipment, and have 18 been reported in indoor air and dust (Staaf and Ostman 2005;Saito et al 2007). …”
Section: Reactions On Chamber Wallsmentioning
confidence: 99%
“…As most PFRs are added to and mixed with, rather than chemically bound to the materials (van der Veen and de Boer, 2012), leaching could occur throughout the lifetime (Marklund et al, 2003) of these products. Reports have indicated that PFRs were ubiquitous in various environmental media, such as water (Chung and Ding, 2009;Bacaloni et al, 2008), air (Carlsson et al, 1997;Saito et al, 2007), dust (He et al, 2015;Stapleton et al, 2009), sediment Ricking et al, 2003), soil (Mihajlovic et al, 2011), and biota samples (Kim et al, 2011;Sundkvist et al, 2010). Furthermore, some of the harmful effects of PFRs on human health cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the background levels of PFRs from materials used for sampling, the vacuum dust bag and the ethanol-soaked cotton used to wipe the vacuum nozzle were extracted with acetone and analyzed by GC/MS to confirm that there were no PFRs peaks (data not shown). Thus, the background level of PFRs was negligible, as described previously (Kanazawa et al, 2010;Saito et al, 2007).…”
Section: Quality Control / Quality Assurancementioning
confidence: 69%
“…TPHP and TCEP are emitted from televisions and computers (Carlsson et al, 2000;Hartmann et al, 2004;Saito et al, 2007). 3.7. Comparison of the results of this study with those of previous studies Table 6 shows the concentrations of PFRs in this study compared with those in previous studies of private homes because PFR concentrations can vary depending on the sampling site (Bergh et al, 2011;Van den Eede et al, 2011).…”
Section: Comparison Of Floor Dust Between 2009 and 2010mentioning
confidence: 99%
See 1 more Smart Citation